The prevalence of gestational diabetes mellitus before and after the implementation of the universal two-child policy in China - Zhu, Hui; Zhao, Zhijia; Xu, Jin; Chen, Yanming; Zhu, Qiong; Zhou, Liming; Cai, Jie; Ji, Lindan (Frontiers in Endocrinology, 2022)
Background: After the universal two-child policy has been fully implemented, challenges regarding pregnancy complications seemed to be more severe in China. This study aimed to evaluate the prevalence of gestational diabetes mellitus (GDM) and the main risk factors for GDM before and after the implementation of the universal two-child policy in China. Methods: A retrospective study was performed with 128,270 pregnant women who delivered at Ningbo Women & Children’s Hospital from January 2010 to December 2020. Logistic regression analysis was applied to estimate the risk factors associated with GDM prevalence. Segmented regression analyses of interrupted time series (ITS) were conducted to assess the effect of the universal two-child policy on the trends of GDM. Results: The prevalence of GDM increased remarkably from 4% in 2010 to 21% in 2020. ITS analysis revealed an upward trend in GDM after the implementation of the universal two-child policy. The proportion of women with advanced maternal age (>30 years) increased by 1.68% per year before the implementation of the universal two-child policy and by 2.32% per year after 2016. Advanced maternal age (>30 years), multigravidity, multiparity, multiple gestation and gestational hypertension were significantly associated with GDM. Advanced age remained an independent risk factor for GDM even after cross stratification with gravidity and parity. Conclusions: The prevalence of GDM maintained a growth trend after the implementation of the universal two-child policy in China. The rise in the proportion of older pregnant women with the change in fertility policy could increase the GDM rate. We recommend having children at a relatively optimal reproductive age when encouraging childbearing.